1
$\begingroup$

I am trying to compute the derivative of this function with respect to V0:

enter image description here

This is the price of a down and out call option, assuming the barrier equal to the level of debt K. In other terms, I need to compute the Delta of this DOC Option, in the case of Barrier=K (neither Barrier higher than K nor Barrier lower than K) and I cannot find this case anywhere in the literature. Furthermore, the derivative of the first two terms of the equation equals N(d1), the delta of a plain vanilla call option. Therefore, I just need the derivative of what is in the parenthesis [...] with respect to V_0.

Can someone of you help me?

Anything will be really appreciated!

$\endgroup$
  • $\begingroup$ Your question is not readable. Can you please use Latex? $\endgroup$ – Gordon Apr 21 '16 at 14:05
  • $\begingroup$ Can you read it now? I apologize, but I am not able to write it in Latex, can you still help me? $\endgroup$ – Livia G Apr 21 '16 at 16:06
  • $\begingroup$ See Page 8 in people.maths.ox.ac.uk/howison/barriers.pdf. Your formula does not look correct to me. $\endgroup$ – Gordon Apr 21 '16 at 18:21
  • $\begingroup$ what I did was taking the formula of a down and out call option in the case of the barrier below the strike K and, as I am going for the case where barrier=K, I substituted the barrier with K. papers.ssrn.com/sol3/… page 15 $\endgroup$ – Livia G Apr 22 '16 at 8:37
  • $\begingroup$ Your formula is not the same as Formula (3) on Page 15 of the paper you referred to. Please double check and revise. Is the + sign before the last term a typo? $\endgroup$ – Gordon Apr 22 '16 at 12:54
1
$\begingroup$

Let \begin{align*} C(S, K, t) = SN(d_1) - e^{-rt}KN(d_2) \end{align*} denote the Black-Scholes call option price with initial asset value $S$, strike $K$, and maturity $t$. Note that \begin{align*} \frac{\partial C}{\partial S} = N(d_1). \end{align*}

For the above barrier option, note that \begin{align*} E_0 &= V_0 N(d_1)-e^{-rt}KN(d_2) -\bigg[V_0 \Big(\frac{K}{V_0}\Big)^{2\lambda}N(d_1^B) -e^{-rt}K \Big(\frac{K}{V_0}\Big)^{2\lambda-2} N(d_2^B) \Big) \bigg]\\ &=C(V_0, K, t) - \Big(\frac{K}{V_0}\Big)^{2\lambda-2}\bigg[\frac{K^2}{V_0}N(d_1^B) -e^{-rt}K N(d_2^B) \Big) \bigg]\\ &=C(V_0, K, t) - \Big(\frac{K}{V_0}\Big)^{2\lambda-2} C\Big(\frac{K^2}{V_0}, K, t \Big). \end{align*} Therefore, \begin{align*} \frac{\partial E_0}{\partial V_0} &=N(d_1) + (2\lambda-2)\frac{K^{2\lambda-2}}{V_0^{2\lambda-1}}C\Big(\frac{K^2}{V_0}, K, t \Big)-\Big(\frac{K}{V_0}\Big)^{2\lambda-2}\frac{\partial C\Big(\frac{K^2}{V_0}, K, t \Big)}{\partial V_0}\\ &=N(d_1) + (2\lambda-2)\frac{K^{2\lambda-2}}{V_0^{2\lambda-1}}C\Big(\frac{K^2}{V_0}, K, t \Big)+\Big(\frac{K}{V_0}\Big)^{2\lambda}N(d_1^B), \end{align*} since \begin{align*} \frac{\partial C\Big(\frac{K^2}{V_0}, K, t \Big)}{\partial V_0} &= \frac{\partial C\Big(\frac{K^2}{V_0}, K, t \Big)}{\partial \frac{K^2}{V_0}}\frac{\partial \frac{K^2}{V_0}}{\partial V_0}\\ &=-\Big(\frac{K}{V_0}\Big)^{2}N(d_1^B). \end{align*}

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.